2022
DOI: 10.3390/admsci12030084
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leaders’ Coaching Skills on Employees’ Happiness and Turnover Intention

Abstract: This study seeks to provide a more comprehensive understanding of how leaders with coaching skills can affect an individual’s turnover intention through the mediating role of happiness. The sample includes 271 individuals from diverse organizations. Based on a survey, employees assessed their leaders’ coaching skills and reported their own happiness and turnover intention. The findings demonstrate that leaders’ coaching skills have a negative impact on employees’ turnover intention and a positive impact on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Also, the result that the diminished meaningfulness of work increases the degree if turnover intention is also consistent with the previous works ( 52 , 59 ). Lastly, the moderating effect of coaching leadership is consistent with the recent works ( 63 , 67 ). The reason why the results are consistent with the previous work is that our arguments are based on the proper and validated theoretical background.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the result that the diminished meaningfulness of work increases the degree if turnover intention is also consistent with the previous works ( 52 , 59 ). Lastly, the moderating effect of coaching leadership is consistent with the recent works ( 63 , 67 ). The reason why the results are consistent with the previous work is that our arguments are based on the proper and validated theoretical background.…”
Section: Discussionsupporting
confidence: 90%
“…This enables followers to develop a positive self-concept within the organization, feeling respected by the organization. Previous studies have reported that coaching leadership is closely and positively associated with employees' psychological wellbeing, job satisfaction, work performance, and organizational citizenship behavior (61)(62)(63)(64)(65)(66)(67).…”
Section: The Moderating Role Of Coaching Leadershipmentioning
confidence: 99%
“…According to one study's findings, the leadership type is imperative in reducing turnover intentions (Aldarmaki and Kasim, 2019). In another study, the outcomes indicate that leaders' coaching abilities have a detrimental effect on employees' turnover intentions (Romão et al, 2022).…”
Section: Managerial Leadership and Turnover Intentionsmentioning
confidence: 99%
“…Thus salesforce retention remains a challenge to keeping the best talent (Westbrook and Peterson, 2020). Retaining talented employees is one of the major concerns for organizations nowadays (Boyer et al, 2020;Romão et al, 2022). Empirical evidence suggested that work engagement is a strong antecedent of employee turnover intention (Azharudeen and Arulrajah, 2021;Bayode and Duarte, 2022;Bufquin et al, 2021;Gomes and Seruca, 2023;Mallin et al, 2022;Peltokorpi and Allen, 2023).…”
Section: Relationship Between Work Engagement and Turnover Intentionmentioning
confidence: 99%